Learning from cosmopolitan digital musicians : identity, musicianship, and changing values in (in)formal music communities - Partti, Heidi (Sibelius-Akatemia, 2012)
This compilation dissertation comprising the summary and four blind peer-reviewed articles examines the culture of music making and musical learning, and the construction of musical identity in the world of digital and virtual media. The main research goal is to increase the knowledge and understanding about where and in what ways do participants in digital technology enabled communities of musical practice learn and use music in the processes of their identity construction, and to reflect upon what implications the answers to these questions can be expected to have in terms of the values and practices within formal music education. The examination proceeds by advancing heuristically a social theory of learning in general, and of so-called communities of practice, in particular, as this theory provides a lens to understand the intertwined relationship between learning, identity construction and participation in communities. The research project was designed as a qualitative study of multiple cases containing strong features of narrative research, and was conducted with the participation of digital musicians who represent different age groups, nationalities and levels of expertise. Two of the cases are online communities: mikseri.net and operabyyou.com. A third case study is a face-to-face group of students and teacher of a Music Performance and Production course at a London-based music college. The research material includes observation field notes, online discussions, video recorded observations and individual interviews. Each article provides a viewpoint into the main problem concerning musical learning and identity work within digital technologies enabled music-related communities. The findings of the research project illustrate how digital music and information technology has opened up new and wider opportunities for musical learning. Concurrently, the findings question the sharp division between highly specialised musical expertise and amateur music making, as well as the divisions between different musical styles and genres, and the various roles of music makers. Digital musicianship appears to be closely related to values both favouring communication and an exchange of musical ideas, and celebrating simultaneous participation in various global and local communities for pursuing individual and social musical identities in more flexible and open ways. In the study, these extensive cultural changes are suggested to manifest a democratic revolution that provides individuals with the access needed to use their intelligence more freely for musical growth and expression, and to share in the values of musical cultures more democratically. However, based on the study's findings, it is also argued that while informal music practices represent essential aspects of our society's community life, they do not necessarily represent ideal models for the music classroom. As such, in order to realise and comprehend the multidimensionality of students' music learning, the study suggests that it is essential for music educators to pay heed to music making inside and outside school, as well as in the whole continuum between the formal and informal poles, and to promote learning that facilitates the construction of identity and ownership of meaning by placing matters of democracy at the centre of attention.

Tämä yhteenveto-osasta sekä neljästä vertaisarvioidusta artikkelista muodostuva artikkeliväitöskirja tarkastelee musiikin tekemistä ja oppimista sekä musiikillisen identiteetin rakentumista digitaali- ja virtuaalimedian maailmassa. Tutkimuksen päätavoitteena on lisätä tietoa ja ymmärrystä siitä, missä ja millä tavoin digitaalisten ja musiikillisten käytäntöyhteisöjen (communities of practice) osallistujat oppivat musiikkia ja käyttävät sitä identiteettityössään. Tutkimuksessa myös pohditaan, millaisia seuraamuksia tutkimuksen esiintuomilla kysymyksillä voidaan odottaa olevan muodollisen musiikkikasvatuksen arvoihin ja käytäntöihin. Oppimisen, identiteetin rakentumisen sekä yhteisöihin osallistumisen välistä suhdetta tarkastellaan oppimisen sosiaalisen teorian näkökulmasta. Tutkimushanke on laadullinen tapaustutkimus, johon sisältyy narratiivisen tutkimuksen piirteitä. Tutkimus tehtiin eri ikäryhmiä, kansallisuuksia ja asiantuntijuuden tasoja edustavien digitaalimuusikoiden keskuudessa. Tutkimus koostuu kolmesta tapauksesta, joista kaksi (mikseri.net ja operabyyou.com) ovat verkkoyhteisöjä. Kolmas tutkittava tapaus on Lontoossa sijaitsevan musiikkioppilaitoksen Music Performance and Production -linjan opiskelijoista ja opettajasta muodostuva ryhmä. Tutkimusaineisto koostuu kenttäjakson aikana kertyneistä muistiinpanoista, tutkittavien verkkoyhteisöjen keskustelualueilta valituista viesteistä, videotallennetuista havainnoista sekä haastatteluista. Kukin artikkeli tarkastelee päätutkimusongelmaa eri näkökulmista pyrkien kuvaamaan ja ymmärtämään digitaaliteknologioiden mahdollistamissa musiikillisissa yhteisöissä tapahtuvaa oppimista ja identiteettityötä. Tutkimushankkeen tulokset osoittavat, että digitaalinen musiikki- ja informaatioteknologia on avannut uusia ja yhä laajenevia mahdollisuuksia musiikilliselle oppimiselle. Tulosten pohjalta voidaan myös kyseenalaistaa tiukka rajanveto pitkälle erikoistuneen musiikillisen asiantuntijuuden sekä harrastuspohjaisen musiikin tekemisen välillä, kuten myös musiikin lajien ja tyylien sekä musiikintekijöiden roolien välillä. Tutkimus osoittaa, että digitaalimuusikkous liittyy arvoihin, jotka edustavat kommunikaatiota ja musiikillisten ideoiden keskinäistä jakamista. Myös samanaikainen osallistuminen erilaisiin globaaleihin ja paikallisiin yhteisöihin on tärkeä osa digitaalimuusikkoutta. Tämä osallistuminen tarjoaa entistä joustavampia ja avoimempia mahdollisuuksia yksilöllisten ja yhteisöllisten musiikillisten identiteettien rakentamiseen. Tässä tutkimuksessa edellä kuvattujen kulttuuristen muutosten ymmärretään heijastelevan 'demokraattista vallankumousta', joka mahdollistaa entistä vapaamman tiedon tuottamisen musiikillisen kasvun ja ilmaisun välineenä sekä musiikkikulttuurien arvojen entistä tasa-arvoisemman jakamisen. Tutkimustulosten pohjalta voidaan kuitenkin väittää, että musiikin oppimisen epämuodolliset käytännöt eivät välttämättä tarjoa malleja musiikin koulussa tapahtuvaan oppimiseen. Musiikkikasvattajien tärkeä tehtävä onkin huomioida sekä koulussa että sen ulkopuolella tapahtuva musiikin tekeminen sekä edistää oppimista, joka tukee identiteetin ja musiikillisen omistajuuden rakentumista.
Keywords: digitaalinen taide; musiikki; muusikkous; uusmedia; musiikkikasvatus; MuTri